Design and simulation of the control circuit for a CMOS imaging sensor with high resolution and dual shutter mode - ZHANG Chi; YU Shi-jie; YOU Zheng (Tongxin xuebao)
A CMOS imaging sensor with high resolution and dual shutter mode for space information acquisition was presented.The theoretical operation principles and characters of rolling shutter and synchronous shutter for the CMOS imaging sensor were analyzed and compared.Design of the control circuit for two shutter modes were proved correct and effective,by analyzing the results from timing simulation and experimental verification.It is concluded that the design of the control circuit is suitable for imaging system on nano-satellite.